Repetitive process based indirect-type iterative learning control for batch processes with model uncertainty and input delay - Tao, Hongfeng; Zheng, Junhao; Wei, Junyu; Paszke, Wojciech (1975- ); Rogers, Eric; Stojanovic, Vladimir
This paper develops an indirect iterative learning control scheme for batch processes with time-varying uncertainties, input delay, and disturbances. In this paper, a predictor based on a state observer is designed to estimate the future state and to compensate for the input delay.
Keywords: batch processes; iterative learning control; input-delay; repetitive processes; robust H? control; linear matrix inequality